The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fendo.2013.00132
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Measurements of Adiponectin by Mass Spectrometry in Bottlenose Dolphins (Tursiops truncatus) with Iron Overload Reveal an Association with Insulin Resistance and Glucagon

Abstract: High molecular weight (HMW) adiponectin levels are reduced in humans with type 2 diabetes and insulin resistance. Similar to humans with insulin resistance, managed bottlenose dolphins (Tursiops truncatus) diagnosed with hemochromatosis (iron overload) have higher levels of 2 h post-prandial plasma insulin than healthy controls. A parallel reaction monitoring assay for dolphin serum adiponectin was developed based on tryptic peptides identified by mass spectrometry. Using identified post-translational modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
(94 reference statements)
1
20
0
Order By: Relevance
“…The above variables were measured photometrically on the Roche Diagnostics Modular Analytics P Module clinical chemistry analyzer (Roche Diagnostics, Indianapolis, IN, USA) at the Animal Health Diagnostic Center at Cornell University. Adiponectin was measured using parallel reaction monitoring (PRM) as described previously (23). …”
Section: Methodsmentioning
confidence: 99%
“…The above variables were measured photometrically on the Roche Diagnostics Modular Analytics P Module clinical chemistry analyzer (Roche Diagnostics, Indianapolis, IN, USA) at the Animal Health Diagnostic Center at Cornell University. Adiponectin was measured using parallel reaction monitoring (PRM) as described previously (23). …”
Section: Methodsmentioning
confidence: 99%
“…Typically a database of confirmed protein sequences (e.g., UniProt Swiss‐Prot), or translated coding sequences (CDS) are utilized. Even low coverage genome sequencing can be used to search marine mammal data with success . Currently, there is no California sea lion genome, and only 86 protein sequences are in the UniProt Knowledge Base.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide identifications of four proteins were validated using stable isotope standard (SIS) peptides synthesized by New England Peptide (Gardner, MA, USA) with isotopically labeled (‘^’; 13 C and 15 N) c‐terminus amino acids: QELENLER^ (dickkopf‐3), TGAQELLR^ (gelsolin), NAPTPQEFR^ (NCAM1), and IISVELPDDAR^ (reelin). Concentration was determined by amino acid analysis and collision energy was optimized as previously described . An aliquot of CSF (60 μL) was digested the same as described above except that a ratio of 1:10 trypsin:protein was used.…”
Section: Methodsmentioning
confidence: 99%
“…Dr. Benjamin Neely et al dive deeper to assess the potential risk of insulin resistance in dolphins with lower levels of high-weight adiponectin ( 5 , 16 ). Previous studies in mice and humans have demonstrated the insulin-sensitizing effect of adiponectin and its decreasing beneficial impact in the face of iron overload.…”
mentioning
confidence: 99%
“…Previous studies in mice and humans have demonstrated the insulin-sensitizing effect of adiponectin and its decreasing beneficial impact in the face of iron overload. Dr. Neeley et al’s discovery of disrupted associations between adiponectin and glucagon in dolphins with high insulin and iron overload, paired with high sequence similarity of dolphin and human adiponectin, continue to support increasing high-weight adiponectin as a potential therapeutic target for people and other animals with these diseases ( 16 ). Dr. Kirsten Eberle et al use their newly developed, dolphin-specific immunoassays to characterize inflammation present in a 46-year old dolphin with metabolic syndrome and iron overload compared to a dolphin without these diseases ( 17 ).…”
mentioning
confidence: 99%